Incidence of sociodemographic: characteristics in the metropolitan mobility: The case of Madrid - García Palomares, Juan Carlos (Anales de Geografía de la Universidad Complutense, 2008)
The aim of this article was to analyze the relationships between mobility and the sociodemographic and economic characteristics of the population. Relations among the migratory component, the structure by ages, or the differentiation according to educational and rent levels and the characteristics of the commuter’s mobility are identified using a spatial perspective focused in the territorial impact of mobility. An analysis, with a municipality scale, in the Community of Madrid was conducted using data from Census of 2001. It was concluded that changes in the sociodemographics structures are part of the untenable mobility in the metropolitan areas, and are related to longer commutes and an increasing use of cars. .